Capital accumulation chain in post-revolutionary Iran. Issue 4 (1st October 2020) - Maljoo, Mohammad
Abstract : The post-revolutionary Iranian society has experienced two simultaneous, contradictory phenomena: the ever-strengthening capitalist class relations accompanied by ever-weakening capitalist production. These twin unaligned tendencies have continually threatened the viability of the post-revolutionary political economy. In order to explain such a situation, I suggest the capital accumulation chain as the main conceptual framework for both tracing the path taken historically, and assessing the possible roads ahead. The capital accumulation chain embraces its six links as necessary structural conditions of possibility for accumulating capital in the post-revolutionary Iranian economy. Seeing through its lens, the post-revolutionary Iranian political economy can be studied as interactions between six conceptual moments: non-exploitative economic oppression, exploitation of labour, exploitation of nature, production in the workplaces, national and international commodity markets' effective demand for commodities produced in the domestic economy, and the transformation of surplus value made in the domestic economy into capital. Depending on the combination of the differentiated historical ways in which the related structure and agency factors interplay with each other in every six-fold chain of links, a variety of CACs with their own peculiarities can possibly emerge. This paper illuminates the Iranian peculiarities as have been shaped in the post-revolutionary era.